Pharmacokinetics of acetaminophen, codeine, and the codeine metabolites morphine and codeine-6-glucuronide in healthy Greyhound dogs - KuKanich, Butch (2010)
The purpose of this study was to determine the pharmacokinetics of codeine and the active metabolites morphine and codeine-6-glucuronide after IV codeine administration and the pharmacokinetics of acetaminophen (APAP), codeine, morphine, and codeine-6-glucuronide after oral administration of combination product containing acetaminophen and codeine to dogs. Six healthy Greyhound dogs were administered 0.734 mg/kg codeine IV and acetaminophen (10.46 mg/kg mean dose) with codeine (1.43 mg/kg mean dose) orally. Blood samples were obtained at predetermined time points for the determination of codeine, morphine, and codeine-6-glucuronide plasma concentrations by LC/MS and acetaminophen by HPLC with UV detection. Codeine was rapidly eliminated after IV administration (T½ =1.22 hr; clearance=29.94 mL/min/kg; volume of distribution=3.17 L/kg) with negligible amounts of morphine present, but large amounts of codeine-6-glucuronide (C(MAX)=735.75 ng/mL) were detected. The oral bioavailability of codeine was 4%, morphine concentrations were negligible, but large amounts of codeine-6-glucuronide (C(MAX)=1952.86 ng/mL) were detected suggesting substantial first pass metabolism. Acetaminophen was rapidly absorbed (C(MAX)=6.74 μg/mL; T(MAX)=0.85 hr) and eliminated (T½=0.96 hr). In conclusion, the pharmacokinetics of codeine were similar to other opioids in dogs with a short half-life, rapid clearance, large volume of distribution, and poor oral bioavailability. High concentrations of codeine-6-glucuronide were detected after IV and oral administration.